The flow of two zinc oxide-eugenol-based endodontic sealers - Ilić Dragan V. (Vojnosanitetski Pregled)
Background/Aim. Endodontic sealers (ES) for obturation are usually prepared with a slight variation of their components both on purpose or unintentionally. Considering that fact, as well as a frequent use of compaction techniques with the applied force to gutta-percha and ES of 1-3 kg, the aim of this study was to investigate the flow of two zinc-oxide eugenol ES in regard to the applied force and a variation of sealer’s components. Methods. The experimental group samples of both ES were prepared according to the manufacturer’s instructions, applied between pair of glass slabs and loaded by weights of 1 and 2 kg, respectively (American National Standard, Specification No. 57). Some samples of one ES were prepared as thick consistency with 10% more powder and some as thin mixture with 10% less powder than the standard prescription. These semples had been exposed to the load of 2 kg. The control group included samples of both ES prepared as standard prescription but exposed to the weight of one glass slab only. The spread ES appeared as a regular circle 10 min upon mixing and weighting. Measuring of the circle diameter was done by an orthodontic ruler. The flow of the used ES was considered the function of its spread diameter. Results. Application of 1 vs 2 kg load for both regularly mixed sealers in the scope of disk diameter (flow) was statistically insignificant (p > 0.05). This means that the stated null hypothesis that there would be no significant difference in flow rate among the regularly mixed sealers at the level of α = 0.05 is accepted. The findings about difference in the disk diameter in regard to mixing variation of Endomethasone indicate that the null hypothesis that there would be no significant difference in flow rate between the regular and thick mixed mass at the level of α = 0.05 is accepted. In the comparison of regular and thin mix a significant difference was noted and the null hypotesis is rejected (p < 0.01). The control group results displayed Roth 801 as less viscous than Endomethasone sealer (p < 0.01). Conclusion. Application of 1 or 2 kg pressure on the samples of both exposed sealers does not significantly affect the flow values as well as comparison of the regular to thick consistency of Endomethasone while comparison of its regular to thin mass shows a significant difference.